An exposition of the legal issues relating to health records management in Nigeria (2012)
Efficient health records management is crucial to health care delivery. Pertinent legal issues are involved in health records management which health records managers must be conversant with to avoid legal liability. This paper discusses legal issues such as access to health records, patient’s confidentiality and retention of health records. It examines the general principles of law governing health records management and also makes reference to the provisions of the relevant laws in Nigeria and elsewhere. It concludes that the law relating to some of these aspects is still evolving in Nigeria as specific legislation on them are absent compared to what obtains in some developed countries. Finally, it calls on stakeholders in the field of health records management to forge a common front to help develop the law in the field as a basis for providing guidelines for health care institutions in the management of health records in Nigeria.